DESIGN AND STATISTICAL EVALUATION OF A MULTIUNIT DELIVERY SYSTEM CONTAINING NISOLDIPINE-SOLUPLUS® SOLID DISPERSION FOR HYPERTENSION CHRONOTHERAPY - Vats, Sandeep Kumar; Gupta, Roop Narayan; Ramaraju, Kalaiselvan; Singh, Romi (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To study the mechanism and factors affecting the design of an industrially scalable formulation in a combined drug delivery module containing solid dispersion (SD) multiunit pellets with novel polymer Soluplus® in a modified release system to address chronotherapeutic needs of hypertension therapy. Methods: Nisoldipine-Soluplus® SD pellet formulations were prepared using the central composite design of experiments (CCD) to study the effect of inert core level and drug to polymer ratio. The solid dispersions were formed on inert pellets surface by fluidized bed coating and characterized by dissolution efficiency and time for 90% drug release. The data was statistically analyzed to develop a response surface for optimum SD formulation in pellets. The SD pellets were characterized by FTIR, DSC and SEM. The optimum formulation of SD coated pellets was further coated with Eudragit S100-L100 polymer mix and characterized for dissolution in multimedia and two-step dissolution for lag time. Results: A response surface was developed for highest dissolution efficiency (%DE) and least time to release 90% drug (T90). The model was significant, and the role of core pellets was found to be more significant than the drug-polymer ratio. The study of the desirability function indicated that a polymer content of 75% and inert core level to yield 23% net weight gain, provided optimum dissolution enhanced SD pellets. The drug was found to exist in amorphous form. The final capsules containing Eudragit S100-L100 coated delayed release SD pellets showed a lag time of 2 h and a definite pH-gradient towards drug release. Conclusion: The findings from this study helped to understand the mechanism, design and factors affecting drug release from a delayed release SD system for a poorly soluble drug for potential hypertension chronotherapy.